Clinico-Radiological Spectrum of Neuronal Migrational Disorders: A Study of Paediatric Patients in the Western Region of Nepal - Swain, PK; Dhaliwal, MS; Thapalial, A; Tiwari, PK (Journal of Nepal Paediatric Society, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objective: This study was conducted in a tertiary care paediatric hospital to ascertain the spectrum of clinical and radiological features of Neuronal Migrational Disorders in children. The role of inheritance in Neuronal Migrational Disorders is under intense investigation. Studies on Neuronal Migrational Disorders (NMDs) in children from developing countries are lacking. Method: Retrospective analysis of records of diagnosed cases by neuroimaging as Neuronal Migrational Disorders in the Department of Paediatrics. Results: Eighteen Children (2days to 8years age) with different types of neuronal migrational disorder based on neuro-imaging were included. Observed anomalies included Lissencephaly (33.3%), Pachygyria (16.6%), Polymicrogyria (5.5%), Heterotopia (11.1%), Schizencephaly (22.2%) and Hemimegalencephaly (5.5%). Focal Seizure in 5 (27.7%) cases, Generalised Tonic Clonic Seizures in 3 (16.6%) and Myoclonic Seizure in 2 (11.1%) cases were the types of seizure present in 10 (55.5%) patients. Five patients presented with Quadriparesis, two with Hemiplegia and one with Congenital Talipes Equinovarus. All the eighteen patients had some degree of Cognitive Developmental Delay. Conclusion: Lissencephaly is the most common type of Neuronal Migrational Disorder followed by Schizencepahly. Focal Seizure and Quadriparesis were the common manifestations. Family history of similar cases with parental consanguinity in Schizencephaly cases gives a clue to the autosomal recessive mode of inheritance. Family history of similar cases of Schizencephaly without any history of consanguinity indicates an autosomal pattern of inheritance. Key words: Neuronal Migrational Disorders, Lissencephaly, Schizencephaly, Cognitive Developmental Delay and Neuro-imaging. DOI = 10.3126/jnps.v28i1.1399 J. Nepal Paediatr. Soc. Vol.28(1) p.10-13